From dental infection to extradural empyema: a case report - Comte Clément; Hasnaoui Nasr (EDP Sciences, 2019)
Introduction: Brain infections of dental origin are rare, but well-known and accurately described. There are two different brain infections: brain abscess, the most frequent, and extradural or subdural empyema. Here, we discuss the case of an extradural empyema. Observation: A 28-year-old man with a very poor dental condition showed neurological and eye infection signs. A brain and face CT scan revealed extradural empyema, orbit abscess and pansinusitis. These infections had all dental origin: an apical lesion of tooth 26. Discussion: Such severe cases must be surgically and medically treated with a strong antibiotic therapy. A systematic investigation and the treatment of dental infected areas are both necessary.